Joyce, "Penelope" and the body - Brown, Richard, 1954- (European Joyce studies, 2006)
Joyce, "Penelope" and the Body is a collection of twelve essays about "Penelope", the famous final episode of Joyce's Ulysses in relation to contemporary literary, cultural, philosophical and psychoanalytical theories of the body. As such it offers an unusually close look at that episode itself and it also becomes the very first book on Joyce that takes the idea of the body as its announced central theme. The contributors represented here come from England, Ireland, Europe and North America and they include some of the best established critics of Joyce alongside newcomers to academic publicati.